JOCRISE PARADIGM: EDUCATION & FALSE CONTROLLING CONCEPTS - Shakespeare, Rodney; Challen , Peter (University of Darussalam Gontor Press, 2024)
Education is generally believed to be the purpose of society. Thus mathematical and linguistic skills are necessary for the production and consumption sectors of the economy thereby benefitting everybody (if only to some extent). Nevertheless, certain political and economic groupings within society only want to benefit themselves rather than everybody else. They can do this via their supporters in higher education, think tanks and mainstream media who promote False Controlling Concepts which have underlying assumptions about reality all of which are claimed to be true. The actuality, however, is the opposite and the falsity serves the economic and financial interests of the groupings while, at the same time, producing distortions, disorders, inefficiencies and injustices in society as a whole. Fortunately, the false assumptions can be reversed to create the JOCRISE Paradigm thereby enabling new solutions to major global problems